POLA PENERAPAN METODE TARGHIB WA TARHIB PADA PEMBELAJARAN TAHSIN TAHFIDZ DI SMPIT BINA INSANI KOTA METRO - Iswati Iswati (AT-TAJDID, 2018)
The application of targhib and tarhib methods in tahsin and tahfidz lessons does not necessarily solve problems that arise in the learning process, because the application of a method has consequences in the form of challenges and obstacles that require a way out.This study aims to explore the pattern of the application of the targhib and tarhib method in tahsin and tahfidz learning at the Bina Insani Middle School in Metro City. The process of collecting data using the method of observation, interviews, and documentation to achieve valid and representative data. The results showed that the implementation of the targhib and tarhib methods in tahsin and tahfidz lessons had a side of effectiveness and problematics but were still in the level of being able to be handled well by schools and teachers. Targhib and Tarhib have given to students at Bina Insani Middle School at Metro City, have been in accordance with the education corridor and have been agreed upon between the School, Teachers, Student, and Student Guardians.